Implementation of the Right to Information Act (RTI-2009) in the selected upazilas of Mymensingh district - Karim, Md. Fakrul (BRAC University, 2014)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2013.